2023
DOI: 10.5187/jast.2022.e114
|View full text |Cite
|
Sign up to set email alerts
|

The roles of growth factors and hormones in the regulation of muscle satellite cells for cultured meat production

Abstract: The roles of growth factors and hormones in the regulation of muscle satellite cells for cultured meat production

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 133 publications
0
1
0
Order By: Relevance
“…[178], [179], [180], [181] Rabbit meat Biological activity; factors affecting quality; meat quality; quality determinants; rabbit breeds [182] Satellite cell Adipogenesis; AKT/AMPK signaling pathway; antimicrobial peptide; apolipoprotein H; blood removal; C2C12 myoblast cell; carcass chilling method; cell growth; chicken; CopA3; culture temperature; cultured meat; differentiation; fat; food safety; genetic analysis; growth factors; Hanwoo; myosatellite cell; hormone-lipid metabolism; meat color; meat quality; muscle satellite [30], [183], [184], [185], [186],…”
Section: Discussionmentioning
confidence: 99%
“…[178], [179], [180], [181] Rabbit meat Biological activity; factors affecting quality; meat quality; quality determinants; rabbit breeds [182] Satellite cell Adipogenesis; AKT/AMPK signaling pathway; antimicrobial peptide; apolipoprotein H; blood removal; C2C12 myoblast cell; carcass chilling method; cell growth; chicken; CopA3; culture temperature; cultured meat; differentiation; fat; food safety; genetic analysis; growth factors; Hanwoo; myosatellite cell; hormone-lipid metabolism; meat color; meat quality; muscle satellite [30], [183], [184], [185], [186],…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that muscle satellite cells can differentiate into muscle cells, adipocytes, osteocytes, or myocytes owing to their multipotential mesenchymal stem cell activity [44]. In addition, muscle satellite cells are the most commonly used cells for cultivated meat production because satellite cells easily differentiate into myotubes and mature myofibrils owing to their regenerative capacity [45][46][47][48][49]. Muscle stem cells are known to have differentiation abilities depending on the species, age, and body part from which they are extracted [50].…”
Section: Muscle Satellite Cellsmentioning
confidence: 99%
“…This process involves MSC activation, proliferation, and the fusion of differentiating myoblasts into mature myofibers under the direction of muscle regulatory factors ( Relaix et al, 2005 ; Zammit and Beauchamp, 2001 ), growth factors ( Allen and Boxhorn, 1989 ), and cytokines ( Spangenburg and Booth, 2002 ) to produce SM tissue. Many studies have described the cell types ( Shaikh et al, 2021 ) and the roles of growth factors ( Ahmad et al, 2023 ) and extracellular matrix (ECM) ( Lim et al, 2021 ) in CM production. However, large-scale CM production depends upon the in vitro production and differentiation of MSCs, as it was concluded in the first report issued on the cultivation of muscle-based beef burgers ( Post, 2012 ).…”
Section: Introductionmentioning
confidence: 99%